Úprava vody s obsahem huminových látek - Pivokonský, Martin; Pivokonská, Lenka; Vašatová, Petra; Janda, Václav (Chemické listy, 2010)
Humic matter is the prevailing constituent of natural organics in many surface water resources. Humic matter is a class of complex polyclic high-molecular-weight compounds with molecular weights ranging from ten thousands to hundred thousands. Humic matter often varies in different types of surface water and for that reason different treatment technologies are used. The most common method is chemical water treatment based on coagulation/ floculation of humic substances. Besides, chemical processes and other methods can be used for removal of humic matter in water treatment, such as sorption, ion exchange, membrane filtration, oxidation and biological methods.
Keywords: Financing, Organized; huminové látky; financování organizované; čištění vody; Humic Substances; Water Purification